Quantitative and qualitative 23Na MR imaging of the Human kidneys at 3 T: before and after a water load - Haneder, Stefan; Konstandin, Simon; Morelli, John N.; Nagel, Armin Michael; Zöllner, Frank G.; Schad, Lothar R.; Schönberg, Stefan; Michaely, Henrik J. M. (Radiology, 2011)
Purpose To qualitatively and quantitatively assess the corticomedullary sodium 23 (23Na) concentration in human kidneys before and after oral administration of a water load by using 3-T magnetic resonance (MR) imaging. Materials and Methods Fourteen healthy volunteers (mean age, 28 years; range, 24-34 years) were included in this institutional review board-approved study between July and December 2009. For 23Na MR imaging, a density-adapted three-dimensional radial gradient echo sequence (echo time, 0.55 msec; repetition time, 120 msec; spatial resolution, 5 × 5 × 5 mm) was used with a dedicated 23Na-tuned coil. Beforehand, the coil profile was assessed by using phantom measurements, and the volunteer images were mathematically corrected accordingly. Images of the volunteers were obtained before and 30 minutes after oral ingestion of 1 L of water. As internal reference, 23Na concentration of the cerebrospinal fluid (CSF) was calculated. Well-defined corticomedullary complexes in each kidney were assessed, with 23Na concentrations in the cortex and medulla assessed at various standardized points. From these values, quantitative 23Na concentrations were derived, and the slopes of the linear portion of the concentration gradient were calculated. Paired t tests were performed. Results Mean calculated 23Na concentrations of CSF before (135.2 mmol/L ± 10.4) and after water load (135.5 mmol/L ± 11.0) fell within physiologic ranges (P = .95). An increase in average 23Na concentration from 63.5 mmol/L ± 9.3 in the cortex to 108.0 mmol/L ± 10.9 in the medulla was identified. After the water load, this gradient was preserved, although 23Na concentrations decreased significantly (P < .0001) to 48.6 mmol/L ± 5.3 in the cortex and 81.9 mmol/L ± 10.1 in the medulla—declines of 23.4% and 24.7%, respectively. Conclusion This study demonstrates the physiologic evaluation of human kidneys with 3-T 23Na MR imaging. The 23Na imaging technique used allows the quantification of the corticomedullary 23Na concentration and the assessment of its change with differing physiologic conditions. © RSNA, 2011 Supplemental material: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.11102263/-/DC1
Im Titel ist "23" bei "Na" hochgestellt
Gesehen am 02.08.2022